Perbedaan Tingkat Kecemasan Siswa Kelas IX Yang Tinggal Bersama Orang Tua Kandung dengan Siswa Yang Tinggal Terpisah dalam Menghadapi Ujian Nasional di Kecamatan Kerjo, Karanganyar - Nindya Putri Permata Risadayu; Istar Yuliadi; Rosalia Sri Hidayati (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Anxiety is the worrying, nervous, fear, and sense of unpeace that is usually associated with danger. National examination as well as living status with biological parents can cause anxiety among 9th grade students. Students who do not live with their biological parents may feel more anxious due to lack of support and direct supervision from parents. This research aims to determine whether level of anxiety differs between 9th grade students who live with their biological parents and those who live apart in facing the national examination in Kerjo Sub-district, Karanganyar. Methods: This was an analytic observational research using cross-sectional approach. Subjects were 9th grade students of SMP Muhammadiyah 5 Kerjo, MTs Muhammadiyah 3 Kerjo, and SMP Negeri 2 Kerjo who either live together with and who live apart from their biological parents. Subjects were initially sampled purposively and later randomly selected based on inclusion and exclusion criteria. Subjects were asked to fill in (1) curriculum vitae form, (2) L-MMPI questionnaire to determine subjects honesty in filling out the questionnaire, (3) T-MAS questionnaire to measure the anxiety scores. Data were analyzed using Chi square (?2) test. Results: Of 34 students living with their biological parents, 28 (82,4%) were anxious. Similarly, 29 (85,3%) of 34 students living apart were also found to be anxious. Statistical analysis for comparison between the two groups showed a ?2 value of 0,108 (p = 0,742). Conclusions: There were no differences of anxiety level between 9th grade students who live with their biological parents and those who live apart in facing the National Examination in Kerjo Sub-district, Karanganyar. Keywords: Students living with biological parents, students living apart from biological parents, anxiety, the national examination.